RESEARCH DEVELOPMENT OF PROCESSING COCOA BEANS - Alam Anshary (AGROLAND: The Agricultural Sciences Journal, 2015)
The purpose of this study is to get a fresh way of processing cocoa beans or cocoa beans are not fermented into (1) dry cocoa bean  with traits such as fermented, (2) powder-paste dry beans with traits such as fermented, through the removal of the pulp and seed coat cocoa, as well as pH and temperature control as well as certain long. Stages of the study consisted of : stages of treatment research 1 Introduction the determination of the cocoa beans before incubation, 2. Determination of treatment introduction to cocoa beans before incubation and incubation media solution pH determination, 3. Determination of treatment introduction to cocoa beans before incubation and incubation media concentration, 4. Incubation process conditions and incubation media concentration. The results showed that the fermentation cocoa with formic acid buffer immersion obtained results with the highest nitrogen index and the highest acidity at a concentration of 48 to 175 mM in incubation buffer using formic acid, are the best conditions for dry cocoa beans. The results of the color index during incubation at 12, 24, 36 and 48 hours of incubation media with 175 mM concentration 0.9440; 0.9952; 1.0961, and 1.1623. So the application of the cocoa beans using Formic acid as a medium 175 mm marinade for non pulp cocoa beans for 36 to 48 hours. Fermented cocoa with acid immersion liquor acetate gives the expected product form acceptable to the consumer. The use of acetate acid is a material that is very cheap and easily available in the market. Key Words : Cacao, cocoa bean, fermentation, processing.